Epidemiology of septo-optic dysplasia with focus on prevalence and maternal age – A EUROCAT study - Garne, E; Rissmann, A; Addor, M; Barisic, I; Bergman, J; Braz, P; Cavero-Carbonell, C; Draper, E; Gatt, M; Haeusler, M; Klungsoyr, K; Kurinczuk, J; et al. (Elsevier, 2018)
Septo-optic nerve dysplasia is a rare congenital anomaly with optic nerve hypoplasia, pituitary hormone deficiencies and midline developmental defects of the brain. The clinical findings are visual impairment, hypopituitarism and developmental delays. The aim of this study was to report prevalence, associated anomalies, maternal age and other epidemiological factors from a large European population based network of congenital anomaly registries (EUROCAT). Data from 29 full member registries for the years 2005–2014 were included, covering 6.4 million births. There were 99 cases with a diagnosis of septo-optic dysplasia. The prevalence of septo-optic dysplasia in Europe was calculated to lie between 1.9 and 2.5 per 100,000 births after adjusting for potential under-reporting in some registries. The prevalence was highest in babies of mothers aged 20–24 years of age and was significantly higher in UK registries compared with other EUROCAT registries (P = 0.021 in the multilevel model) and the additional risk for younger mothers was significantly greater in the UK compared to the rest of Europe (P = 0.027). The majority of septo-optic dysplasia cases were classified as an isolated cerebral anomaly (N = 76, 77%). Forty percent of diagnoses occurred in fetuses with a prenatal diagnosis. The anomaly may not be visible at birth, which is reflected in that 57% of the postnatal diagnoses occurred over 1 month after birth. This is the first population based study to describe the prevalence of septo-optic dysplasia in Europe. Septo-optic dysplasia shares epidemiological patterns with gastroschisis and this strengthens the hypothesis of vascular disruption being an aetiological factor for septo-optic dysplasia.